Heating Performance of Solar Heat Pump Heating System With Aluminum Tube Collector - Wu Zhenkui; Yang Peihong; Jiang Hui; Wei Yili; Zhang Jihong; Zhang Zilei; Zhang Xiaoming (IEEE Access, 2021)
A solar heat pump heating system with an aluminum tubular collector is proposed in this paper. Mathematical models are established for solar energy absorption and air energy absorption of the aluminum tubular collector, as well as the heat-absorption coefficient of the working substance. The electronic expansion valve is controlled via the fuzzy PID method to adjust the working substance flow rate, as well as to control the evaporator overheating and set the indoor heating temperature. TRNSYS is used to analyze the effects of the wind speed, solar radiation amount, environment temperature, and working substance flow rate on the heat transfer performance of the aluminum tubular collector. The results indicate that the heat transfer performance of the aluminum tubular collector is significantly affected not only by the solar radiation but also the wind speed. For wind speed > 2 m/s, the absorbed power of the collector increases rapidly with an increase in the wind speed; when the working-medium flow rate reaches 4 m/s, the collector absorption power tends to be saturated. Subsequently, an experimental heating system with a heating area of 170 m2 is constructed. Experiments revealed that the maximum coefficient of performance (COP) of the heating system is 4.46, and the average COP value is 3.95, indicating good heating effect.